Laser-induced fusion detonation wave. (11th April 2016) - Eliezer, S.; Ravid, A.; Henis, Z.; Nissim, N.; Martinez Val, J.M.
Abstract: Development of a detonation wave due to α heating following short pulse laser irradiation in pre-compressed deuterium–tritium (DT) plasma is considered. The laser parameters required for development of a detonation wave are calculated. We find that a laser irradiance and energy of I L = 1.75 × 10 23 W/cm 2 and 12.8 kJ accordingly during 1.0 ps in a pre-compressed target at 900 g/cm 3 creates an α heating fusion detonation wave. In this case, the nuclear fusion ignition conditions for the pre-compressed DT plasma are achieved along the detonation wave orbit.